STRUCTURE OF DIAGNOSTIC ABILITIES OF SOCIAL TEARCHER - Korniat, Vira S. (Educological discourse, 2014)
In the article the problem of professional preparation is examined social tearcher to implementation by them functional duties, in particular forming of necessary professional abilities. Basic functions and directions of activity of social teacher are described, the separate looks of research workers are exposed to maintenance and essence of diagnostic abilities of teachers. On the basis of analysis of scientific researches the author structure of diagnostic abilities of social teacher is offered, its maintenance is exposed.